1996
DOI: 10.1159/000113197
|View full text |Cite
|
Sign up to set email alerts
|

The Predatory Strike of Free Ranging Praying Mantises, <i>Sphodromantis lineola </i>(Burmeister). II: Strikes in the Horizontal Plane

Abstract: The predatory behavior of free ranging praying mantises, Sphodromantis lineola (Burmeister), in response to prey at various positions in the horizontal plane was examined using high speed (200 frames per second) videography: We found that the movements of the meso- and metathoracic legs over the course of the strike were analogous in many respects to those made by the cockroach Periplaneta americana during escape turns. When mantises struck at prey directly ahead of them, they were propelled forward by extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…However, in any particular event the sequence might be head orient-track-stalk-lunge-strike, or track-adjust posture-lunge-strike, or track-strike, or simply strike if the prey moves close to the mantid. On the other hand, if prey is moving away, the sequence might be prothorax orient-track-track-chase-stalk-track-stalk-lungestrike(miss)-stalk-adjust posture-strike(capture) Cleal and Prete, 1996;Prete and Cleal, 1996]. We imagine the putative DCMD-like cells playing their key role only in initiating the strike component in such sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in any particular event the sequence might be head orient-track-stalk-lunge-strike, or track-adjust posture-lunge-strike, or track-strike, or simply strike if the prey moves close to the mantid. On the other hand, if prey is moving away, the sequence might be prothorax orient-track-track-chase-stalk-track-stalk-lungestrike(miss)-stalk-adjust posture-strike(capture) Cleal and Prete, 1996;Prete and Cleal, 1996]. We imagine the putative DCMD-like cells playing their key role only in initiating the strike component in such sequences.…”
Section: Discussionmentioning
confidence: 99%
“…This means that by itself the position of prey within the visual field does not necessarily indicate its position in relationship to the prothoracic legs which must grasp the prey, or the pterothoracic legs which must direct the lunge (if one occurs). In fact, kinematic analyses have revealed that mantids locate and strike at prey within a large three-dimensional area that requires them to modulate both the reach of the striking prothoracic legs, and the direction and distance spanned by the lunge Cleal and Prete, 1996;Prete and Cleal, 1996;Prete and Hamilton, 1999]. Therefore, prey position in the visual field at the beginning of the strike is meaningful only to the extent that the visual information is integrated with proprioceptive information indicating the relative positions of the head and prothorax.…”
Section: A General Model Of Mantid Prey Capturementioning
confidence: 99%
“…If the prey is sufficiently close, they strike it with rapid grasping movements of forelegs. The strike is occasionally accompanied with a displacement of the body, called lunge (Copeland and Carlson, 1979;Corrette, 1990;Prete and Cleal, 1996;Cleal and Prete, 1996). During these events, the mantis' central nervous system (CNS) extracts spatial characteristics about the prey (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…During a lunge, the movement of the mid‐ and hind legs propel the mantis body in the direction of the prey. The amplitude and direction of both strikes and lunges are adjusted depending on the three‐dimensional position of the prey (Copeland & Carlson, ; Corrette, ; Cleal & Prete, ; Prete & Cleal, ; Oufiero et al ., ). These movements allow for a wide catching range.…”
Section: Predatory Behavioursmentioning
confidence: 99%